2011
DOI: 10.1007/s10096-011-1175-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of an MRSA outbreak in a neonatal intensive care unit

Abstract: Abstract:We report an MRSA outbreak in our 25 bed tertiary neonatal intensive care unit (NICU), which was successfully contained. Patients and Methods: retrospective review of patient files, microbiology records and meeting protocols. Results: During the seven months of outbreak, 27 patients and 7 health care workers (HCWs) had positive cultures for MRSA. The outbreak was caused by the epidemic Rhine-Hessen strain, cultured isolates were monoclonal. After a sharp increase of the number of new MRSA-cases the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
0
13
0
5
Order By: Relevance
“…In the second phase, all endemic epidemic isolates with typical phage patterns were excluded from the study, and only 136 strains that showed deviating autonomous phage patterns or were nontypeable by phages were included in the analysis in a blind fashion and were spa typed later (13). PFGE of 38 outbreak isolates and CC22 isolates was performed as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second phase, all endemic epidemic isolates with typical phage patterns were excluded from the study, and only 136 strains that showed deviating autonomous phage patterns or were nontypeable by phages were included in the analysis in a blind fashion and were spa typed later (13). PFGE of 38 outbreak isolates and CC22 isolates was performed as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate the method further, 38 strains isolated during an outbreak of ST225 MRSA (14) were retrospectively characterized by MALDI-TOF MS. Thirty-three isolates were assigned to CC5 and one MSSA strain, one unrelated MRSA strain, and one BORSA strain isolated from health care workers were correctly identified as unrelated strains. The CC5 biomarker m/z 3,891 was shifted to m/z 3,875 in the MRSA and MSSA isolates, and the BORSA strain contained the A27V exchange in GraC.…”
Section: Fig 2 Overview Of the Maldi-tof Mass Spectra Of Two Closely mentioning
confidence: 99%
“…Doctor Barrett predicted that ''methicillin-resistant staphylococci will become more widespread in the United States and may present some clinical and epidemiologic problems in the future'' [19]. This forecast was correct: The following four decades were replete with instances of MRSA outbreaks in the community, hospital wards, nursing facilities, and, ubiquitously, medical, surgical, and neonatal intensive care units (ICUs) [15,[20][21][22][23][24][25][26][27]. The 1980s saw the arrival of MDROs expressing resistance to progressively newer antibiotics.…”
Section: Contemporary Eramentioning
confidence: 99%
“…This has proved effective for disrupting outbreaks of MRSA [21,22,26,27], VRE [38,39,[41][42][43], ESBL-producing K. pneumoniae [30,[32][33][34], S. marcescens [44], Acinetobacter baumannii [31,[45][46][47], and P. aeruginosa [48].…”
Section: Cohorting and Outbreak Controlmentioning
confidence: 99%
“…Ein bakterielles Pathogen, das auch in NICUs als Ausbruchserreger mit einer erheblichen Morbidität und mit einem massiven Mehraufwand zur Eindämmung der nosokomialen Übertragung einhergehen kann, ist S. aureus, insbesondere, wenn es sich bei dem Ausbruchsstamm um ein methicillinresistentes Isolat handelt [13,14] 28.02.2013). Einschlusskriterien waren englisch-und deutschsprachige Veröffentlichungen aus Europa, den USA, Kanada und Australien.…”
unclassified